Prenatal exposure to endocrine disrupting chemicals is associated with altered DNA methylation in cord blood. Issue 9 (2nd September 2022) - Mattonet, Katharina; Nowack-Weyers, Nikola; Vogel, Vanessa; Moser, Dirk; Tierling, Sascha; Kasper-Sonnenberg, Monika; Wilhelm, Michael; Scherer, Michael; Walter, Jörn; Hengstler, Jan G.; Schölmerich, Axel; Kumsta, Robert
ABSTRACT: Prenatal exposure to endocrine disrupting chemicals can interfere with development, and has been associated with social-cognitive functioning and adverse health outcomes later in life. Exposure-associated changes of DNA methylation (DNAm) patterns have been suggested as a possible mediator of this relationship. This study investigated whether prenatal low-dose exposure to polychlorinated biphenyls (PCBs) and polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) is associated with altered DNAm patterns across the genome in a Western urban-industrial population. In 142 mother-infant pairs from the Duisburg Birth Cohort Study, PCBs and PCDD/Fs levels were quantified from maternal blood during late pregnancy and associated with DNAm levels in cord blood using the Illumina EPIC beadchip. The epigenome-wide association studies (EWAS) identified 32 significantly differentially methylated positions (DMPs) and eight differentially methylated regions (DMRs) associated with six congeners of PCB and PCDD in females or males (FDRs < 0.05). DMPs and DMRs mapped to genes involved in neurodevelopment, gene regulation, and immune functioning. Weighted gene correlation network analysis (WGCNA) showed 31 co-methylated modules (FDRs < 0.05) associated with one congener of PCDF levels in females. Results of both analytical strategies indicate that prenatal exposure to PCBs and PCDD/Fs is associated with altered DNAm of genes involved in neurodevelopment, gene expression and immune functioning. DNAm and gene expression levels of several of these genes were previously associated with EDC exposure in rodent models. Follow-up studies will clarify whether these epigenetic changes might contribute to the origin for adverse mental and health outcomes.